Tocqueville e Gobineau no Mundo dos Iguais - Helga Gahyva (Universidade do Estado do Rio de Janeiro, 2006)
The article aims to analyze how two apparently dissimilar authors like Alexis de Tocqueville and Arthur de Gobineau reached similar conclusions concerning the future possibilities launched by the modern experience. The suggestion is that one of the clues for understanding this similarity lies in the influence both received from the argument of the 18th century nobility´s reaction in the discussion that became known as the quarrel of the two races.